Scale Development and Validation for Measuring Organizational Readiness in order to Implement Social Intranet (A Study in Fars Regional Electric Company) - habib allah Ranaei Kordshooli; mehdi ghahramanifard (Journal of Information Technology Management)
One of the organizations’ concerns is their awareness about the degree of readiness for implementing social intranet. In response to this problem, a 48 item questionnaire was developed. Fars Regional Electric Company consisting of 820 human resources was selected as statistical population. By systematic random method, 262 personnel were determined as sample and the developed questionnaire were distributed among them. Construct validity was measured by conformity factor analysis and reliability of questionnaire was measured by Cronbach’s alpha and finally 43 item were confirmed. Results showed that Fars Regional Electric Company enjoys the proper organizational culture, policy and procedure and organizational resource, but personal experience of people in social intranet area is low and organizational structure also doesn't have necessary characteristics for implementation of social intranet. Finally suggestions were introduced for improving company readiness in implementation of social intranet.